Mechanically activating formation of layered structured bismuth titanate - Stojanovic, B. D.; Paiva-Santos, C. O.; Jovalekic, C.; Simoes, A. Z.; Filho, F. M.; Lazarevic, Z.; Varela, José Arana [UNESP] (Elsevier B.V., 2006)
Bismuth titanatc-Bi(4)Ti(3)O(12) (BIT) with wide application in the electronic industry as capacitors, memory devices and sensors is the simplest compound in the Aurivillius family, which consists of (Bi(2)O(2))(2+) sheets alternating with (Bi(2)T(i)3O(10))(2-) perovskite-like layers. The synthesis of more resistive BIT ceramics would be preferable advance in obtaining of well-densified ceramic with small grains randomly oriented to limit the conductivity along the (Bi(2)O(2))(2+) layers. Having in mind that the conventional ceramic route for the synthesis can lead to non-stoichiometry in composition, in consequence of the undesirable loss in bismuth content through volatilization of Bi(2)O(3) at elevated temperature, our efforts were addressed to preparation of BIT by mechanical activation the constituent oxides. The nucleation and phase formation of BIT, crystal structure, microstructure, powder particle size and specific surface area were followed by XRD, Rietveld refinement analysis, thermal analysis, scanning electron microscopy (SEM) and the BET specific surface area measurements. (c) 2005 Elsevier B.V. All rights reserved.
Keywords: ceramics; milling; X-ray diffraction; crystal structure; microstructure